DEVELOPMENT OF PHYSICS E-MODULES BASED ON A SCIENTIFIC APPROACH USING SIGIL SOFTWARE FOR STUDENTS OF CLASS X SMA/MA - Nurul Hikmah Hidayah; Yurnetti Y; Desnita D; Murtiani M (Universitas Negeri Padang, 2022)
The implementation of learning during the COVID-19 pandemic meant that the learning process that was initially carried out in person must be carried out towards distance learning (online). Of course, this requires different preparations, both before the start of the apprenticeship and during it. To adjust the circumstances that occur, we need teaching material based on a Scientific Approach that can help students to be able to learn autonomously. This research aims to reveal the value of the validity and practicality of the electronic physics module based on the scientific approach that was developed.The type of research carried out is research and development or Research and Development (R&D) using the Plomp model that is limited to the one-to-one evaluation stage. The research instrument used a questionnaire in the form of content and construct validity cards. The developed electronic module was validated by five validators, including three physics professors and two physics professors at SMA Negeri 5 Solok Selatan and six students at SMA Negeri 5 Solok Selatan. Data analysis used Cohen's Kappa moment value for validity and practicality.Based on the data analysis, the validity test results were 0.89 with a very valid category. The practicality test scores for students are 0.90 in the very practical category and 0.86 for educators are in the very practical category. It can be concluded that the electronic physics module based on the scientific approach using the Sigil software is valid and practical for the X SMA/MA class students.